2004
DOI: 10.1584/jpestics.29.184
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids and Rice Architecture

Abstract: Studies on brassinosteroid (BR) function in dicot plants have provided definitive proof that BRs regulate a broad range of cellular responses, and revealed that BRs are essential for plant development and growth. However, prior to our studies of BR mutants of rice, there had been no reports dealing with the molecular biological function of BRs in monocot plants. We have isolated and characterized three independent BR-related mutants of rice. All three exhibit a common phenotype: erect leaves, shortened interno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
(29 reference statements)
1
35
1
1
Order By: Relevance
“…One maize BR-deficient phenotype demonstrated in this work is increased leaf angle, as reported previously of BR-deficient mutants in rice (Hong et al, 2004). Upright leaves are an agronomically important trait that contributed to increased planting densities and yield increases achieved by modern maize hybrids (Duvick, 2005).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…One maize BR-deficient phenotype demonstrated in this work is increased leaf angle, as reported previously of BR-deficient mutants in rice (Hong et al, 2004). Upright leaves are an agronomically important trait that contributed to increased planting densities and yield increases achieved by modern maize hybrids (Duvick, 2005).…”
supporting
confidence: 78%
“…This regulation not only contributes to the diversity of plant form and the adaptation of plants to their environments (Orshan, 1986;Chapin et al, 1987) but has been central to major gains in crop yield in the 20th and 21st centuries (Salamini, 2003;Salas Fernandez et al, 2009). Phytohormone regulation of plant architecture and components such as plant height, branching, and floral organ development has been studied extensively (Evans and Poethig, 1995;Choe et al, 2001;Hong et al, 2004;Sakamoto et al, 2006). The simultaneous presence of multiple phytohormones in all plant tissues raises the question: how do interactions between these developmental determinants influence the plant form?…”
mentioning
confidence: 99%
“…Previous studies showed that abnormal cellular development, such as lacking the longitudinal elongation or increased cell expansion of the adaxial cells in the collar, will result in altered leaf angles [4][5][6]. Indeed, observation of the cross and longitudinal sections revealed increased cell layers at the adaxial surface of the lc2-1 lamina joint, indicating that the enlarged leaf inclination resulted from increased cell division ( Figure 1E).…”
Section: Resultsmentioning
confidence: 76%
“…The lamina joint contributes significantly to the blade bending horizontally from the main axis, and abnormal development of the collar will result in changed leaf angles. Lack of longitudinal elongation in the collar resulted in the erect leaf [4]; conversely, increased cell expansion of collar adaxial cells resulted in the enhanced leaf inclination [5,6], indicating the importance of collar development in leaf angle formation.…”
Section: Introductionmentioning
confidence: 99%
“…To our surprise, we showed that GA inhibits lamina inclination, and the inhibition becomes more obvious in plants with accumulated BR or enhanced BR signaling. It is known that defective elongation/ division of the abaxial cells at the lamina joint usually leads to erect leaves, a characteristic of BR-deficient mutants in rice (Hong et al, 2004;Duan et al, 2006;Zhao et al, 2010), which is not obvious and rarely reported in GA-deficient mutants. One possibility for the inhibition is likely due to the feedback inhibition of GA on the BR response, as lamina inclination was thought to be a BR-specific response.…”
Section: Discussionmentioning
confidence: 99%